2020
DOI: 10.1097/aud.0000000000000985
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Electrocochleography, Angular Insertion Depth, and Cochlear Implant Speech Perception Outcomes

Abstract: Objectives: Electrocochleography (ECochG), obtained before the insertion of a cochlear implant (CI) array, provides a measure of residual cochlear function that accounts for a substantial portion of variability in postoperative speech perception outcomes in adults. It is postulated that subsequent surgical factors represent independent sources of variance in outcomes. Prior work has demonstrated a positive correlation between angular insertion depth (AID) of straight arrays and speech perception un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 45 publications
3
45
1
Order By: Relevance
“…Importantly, recent work has established that there are likely differential effects dependent on array design (i.e., lateral wall vs precurved) (10,11). When restricting this analysis to lateral wall arrays, studies have shown a positive correlation between AID and speech recognition (6)(7)(8)(9)(10)15,18). This is generally understood to be related to beneficial effects of a closer alignment between the electric speech information and tonotopic organization of the cochlea (18)(19)(20)(21)(22)(23)(24), in addition to distributing speech information across greater channel spacing -theoretically allowing for excitation of discrete neuronal populations (e.g., reduced channel interaction) (18).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, recent work has established that there are likely differential effects dependent on array design (i.e., lateral wall vs precurved) (10,11). When restricting this analysis to lateral wall arrays, studies have shown a positive correlation between AID and speech recognition (6)(7)(8)(9)(10)15,18). This is generally understood to be related to beneficial effects of a closer alignment between the electric speech information and tonotopic organization of the cochlea (18)(19)(20)(21)(22)(23)(24), in addition to distributing speech information across greater channel spacing -theoretically allowing for excitation of discrete neuronal populations (e.g., reduced channel interaction) (18).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies investigating the influence of electrode array insertion depth on speech recognition are conflicting, with some demonstrating a decrement in performance with deeper insertions (1,4,13), and others showing a benefit (6)(7)(8)(9)15,17,18). Importantly, recent work has established that there are likely differential effects dependent on array design (i.e., lateral wall vs precurved) (10,11). When restricting this analysis to lateral wall arrays, studies have shown a positive correlation between AID and speech recognition (6)(7)(8)(9)(10)15,18).…”
Section: Introductionmentioning
confidence: 99%
“…There were no surgical factors accounted for within this study. Previous studies have shown that greater insertion depths (13) and scala tympani insertions (3,11,28–32) are correlated with superior speech-perception performance. The location of the electrode within the cochlea likely matters, and investigations are underway examining these factors to build a multivariate model using promontory ECochG-TR to predict CI performance.…”
Section: Discussionmentioning
confidence: 99%
“…Our present study provides a new application of post-operative ECoG in monitoring residual hearing and understanding the pathophysiology of delayed hearing loss. In a future study, we will explore further applications of post-operative ECoG, including the relationship between post-operative ECoG and speech perception, as most data in the literature focuses interoperative ECoG at time of surgery and correlating that with outcome measures (Fontenot et al, 2019, Canfarotta et al, 2021; Walia et al, 2022). In addition, while our measures were conducted using in-house custom-built equipment, cochlear implant companies are also designing and implementing hardware and software adaptations so that their own systems can be used for ECoG recordings.…”
Section: Discussionmentioning
confidence: 99%
“…CM and ANN thresholds correlate strongly with behavioral audiometric thresholds (Abbas et al, 2017; Koka et al, 2017), which can aid with programming the hearing aid portion of the EAS sound processor (Agrawal et al, 2021). Intraoperative measures of ECoG are used to guide cochlear implantation to minimize cochlear trauma (Bester et al, 2022; Lenarz et al, 2022) and have been shown to correlate with post-operative speech understanding (Fontenot et al, 2019; Canfarotta et al, 2021; Walia et al, 2022). One important aspect of ECoG that hasn’t been sufficiently validated is the long-term stability of these measures.…”
Section: Introductionmentioning
confidence: 99%